Future Generation Information Technology 4th International Conference, FGIT 2012, Gangneug, Korea, December 16-19, 2012. Proceedings - Kim, Tai-hoon.; Lee, Young-hoon.; Fang, Wai-chi.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book comprises selected papers of the 4th International Conference on Future Generation Information Technology, FGIT 2012, held in Gangneug, Korea, in December 2012. The papers presented were carefully reviewed and selected from numerous submissions and focus on the various aspects of advances in information technology. They were selected from the following 11 conferences: BSBT 2012, CGAG 2012, DCA 2012, DTA 2012, EL 2012, FGCN 2012, GDC 2012, IESH 2012, IUrC 2012, MulGraB 2012, and UNESST 2012.
Frequency Sharing Method for High Frequency Ocean Surface Radar Using Matched Filtering and Orthogonal Waveforms -- Vertical Handover Security in 4G Heterogeneous Networks: Threat Analysis and Open Challenges -- Three-Dimensional Stacked Memory System for Defect Tolerance -- VCPU Shaping for Supporting Latency Sensitive Workloads -- Architecture for Convergence Mobile Cooperation Service Using Components Integration.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Computer Communication Networks; Software Engineering; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity